(untitled) (American Journal of Multidisciplinary Research and Innovation, 2024)
The purpose of this study is to explore the behavioral intention (BI) of Nepalese cryptocurrency users. Perceived ease of use and perceived usefulness are the constructs from the technology acceptance model; similarly, the trust and the perceived risk are integrated constructs based on literature to predict BI. A close-ended questionnaire survey was a five-point Likert scale. Non-probabilistic purposive sampling , 272 valid responses were analyzed using the statistical package for the social science software, which included Pearson correlation and multiple regression. The result reveals that perceived usefulness, trust, and perceived risk are the significant predictors of BI, however insignificant in relation to perceived ease of use. While consumers have shown positive behavioral intentions toward cryptocurrency, the government has insisted that the restriction is in effect. So, there seems to be a conflict between the practicability of government and the psychology of users. To cope with this, policymakers need to conduct real practice-based studies.